THE EFFECT OF PRACTICE WORK, SELF-EFFICACY AND WORK MOTIVATION ON THE WORK READINESS OF GENERATION Z STUDENTS IN THE FACULTY MALIKUSSALEH UNIVERSITY OF ENGINEERING - Hasanah; Yusniar; Yanita; Azhar (RADJA PUBLIKA, 2025)
This study aims to determine the effect of internship, self-efficacy, and work motivation on the work readiness of generation Z students at the Faculty of Engineering, Malikussaleh University. The data used in this study are primary data obtained by distributing questionnaires to 100 respondents. The data analysis technique used is multiple linear regression analysis using the Statistical Program for Product and Service Solution (SPSS) version 29 software. All variables are measured using a Likert scale. The results of the study indicate that there is a positive and significant influence between internship, self-efficacy, and work motivation on the work readiness of generation Z students at the Faculty of Engineering, Malikussaleh University. This study shows that internship, self-efficacy, and work motivation partially affect the work readiness of generation Z students at the Faculty of Engineering, Malikussaleh University.